1959
DOI: 10.1161/01.cir.20.3.343
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cor Pulmonale in Delhi

Abstract: The incidence of chronic cor pulmonale in Indian states, including Delhi, is the highest reported in nonindustrial populations. The patients presented as acute severe congestive heart failure and at younger ages than those reported. In amany eases there was only a short history of respiratory symptoms. Following the first attack of failure, repeated attacks were the rule and death ensued within 2 years. A study is presented of 127 patients of this type in Delhi with clinical and laboratory data and autopsy dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 1 publication
(1 reference statement)
0
26
0
2
Order By: Relevance
“…This is despite the fact that only 10% of women are smokers compared to 75% of men. Another point to note is that chronic cor pulmonale occurs 10-15 years earlier in women than in men (29). Various Indian studies have calculated a relative risk of 2-4 for biomass fuel exposure (6).…”
Section: Copdmentioning
confidence: 99%
“…This is despite the fact that only 10% of women are smokers compared to 75% of men. Another point to note is that chronic cor pulmonale occurs 10-15 years earlier in women than in men (29). Various Indian studies have calculated a relative risk of 2-4 for biomass fuel exposure (6).…”
Section: Copdmentioning
confidence: 99%
“…seen in 80% cases and engorged neck veins in 71.3% cases. Padmavathi et al 11 reported loud P2 in 65% of cases whereas it was of 57% according to Guptha et al 12 Most important symptom of our study was cough with sputum which reveals the fact that chronic bronchitis with emphysema, bronchiectasis and pulmonary tuberculosis constituted the primary cause in most of the cases. Dyspnoea of grade IV was observed in 60% of cases.…”
Section: Resultsmentioning
confidence: 45%
“…Padmavathi et al 11 reported dyspnea in 100% of group. Cyanosis of central origin was present only in 20% of our cases but it was 80% in Viswanathan series 8 , 83.2% in Padmavathi series 11 and 50 % in Guptha series. 12 In the present study the commonest ECG abnormality was P-pulmonale in patients presenting with congestive cardiac failure.…”
Section: Resultsmentioning
confidence: 95%
“…16 8. Chest X-ray Chest x-ray findings showed chronic bronchitis in 49% and emphysema in 49%, because in the present series only the COPD patients were included.…”
Section: Physical Examinationmentioning
confidence: 99%